Symptoms of Feeding Problems in Preterm-born Children at 6 Months to 7 Years Old. Issue 3 (March 2019) - Park, Jinhee; Thoyre, Suzanne M.; Pados, Britt F.; Gregas, Matt
ABSTRACT: Objectives: Describe symptoms of feeding problems in children born very preterm (<32 weeks gestation) and moderate to late preterm (32–37 weeks gestation) compared to children born full-term; explore the contribution of medical risk factors to problematic feeding symptoms. Methods: The sample included 57 very preterm, 199 moderate to late preterm, and 979 full-term born children ages 6 months to 7 years. Symptoms of feeding problems were assessed using the Pediatric Eating Assessment Tool and compared between groups after accounting for the child's age and/or sex. With the sample of preterm children, we further analyzed 11 medical factors as potential risk factors affecting a child's feeding symptoms: feeding problems in early infancy and conditions of oxygen requirement past 40 weeks of postmenstrual age, congenital heart disease, structural anomaly, genetic disorder, cerebral palsy, developmental delay, speech-language delay, sensory processing disorder, vision impairment, or symptoms of gastroesophageal reflux. Results: Compared to children born full-term, both very preterm and moderate to late preterm born children had significantly higher scores on the Pediatric Eating Assessment Tool total scale and all 4 subscales. More severe symptoms were noted in very preterm children, particularly in the areas of Physiologic Symptoms and Selective/Restrictive Eating. Among preterm children, all 11 medical factors were found to be associated significantly with increased symptoms of feeding problems. Conclusion: Compared to children born full-term, preterm born children demonstrated greater symptoms of feeding problems regardless of their current age, suggesting children born preterm may require more careful monitoring of feeding throughout childhood. Abstract : Supplemental Digital Content is available in the text